2007
DOI: 10.1186/1471-2164-8-384
|View full text |Cite
|
Sign up to set email alerts
|

A systems-biology analysis of isogenic megakaryocytic and granulocytic cultures identifies new molecular components of megakaryocytic apoptosis

Abstract: Background: The differentiation of hematopoietic stem cells into platelet-forming megakaryocytes is of fundamental importance to hemostasis. Constitutive apoptosis is an integral, yet poorly understood, facet of megakaryocytic (Mk) differentiation. Understanding Mk apoptosis could lead to advances in the treatment of Mk and platelet disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 75 publications
1
24
0
Order By: Relevance
“…We have recently shown that GADD45a is up-regulated in human megakaryocytic cells undergoing terminal differentiation (41). However, we have not yet validated a functional role of GADD45a on megakaryocytic differentiation.…”
Section: P53 In Mk Differentiationmentioning
confidence: 92%
“…We have recently shown that GADD45a is up-regulated in human megakaryocytic cells undergoing terminal differentiation (41). However, we have not yet validated a functional role of GADD45a on megakaryocytic differentiation.…”
Section: P53 In Mk Differentiationmentioning
confidence: 92%
“…Thus, immunofluorescence coupled to mean fluorescent intensity quantification was chosen for quantitating the levels of several proteins, a well established method for quantitating protein expression on a single-cell basis (34 -36). Immunofluorescence staining was performed as described by Kodiha et al (37) (38 -42), as well as from our own laboratory (43)(44)(45). Quantification was performed within the cell perimeter only; to delineate the cell borders, 5 M Syto13 (Life Technologies number S7575) or Syto40 (Life Technologies number S11351) was used.…”
Section: Megakaryocyte Cultures and Exposure Of Mk Cells To Shearmentioning
confidence: 99%
“…We mined the RNA sequencing data for genes already defined by others as megakaryocyte-specific and genes highly expressed during megakaryocyte differentiation. 23,24 Of the 56 genes curated by the Papoutsakis group as being megakaryocyte related by literature review, 24 were deregulated by loss of both MKL1 and …”
Section: Rna Sequencing Reveals Srf-independent Functions For Mrtfs Imentioning
confidence: 99%